2020
DOI: 10.1101/2020.10.19.345538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Juvenile corals inherit mutations acquired during the parent’s lifespan

Abstract: 128 years ago, August Weismann proposed that the only source of inherited genetic variation in animals is the germline1. Julian Huxley reasoned that if this were true, it would falsify Jean-Baptiste Lamarck′s theory that acquired characteristics are heritable2. Since then, scientists have discovered that not all animals segregate germline cells from somatic cells permanently and early in development3. In fact, throughout their lives, Cnidaria4-6 and Porifera7 maintain primordial stem cells that continuously gi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…If we had found only separate parent and sperm SNVs this would have shown that Acropora corals have classical Weismannian germ and somatic cell lineage differentiation at the embryonic stage, which has been suggested previously 17 . Likewise, if we had found that all parent tissue SNVs were also in the sperm, we would have concluded that Acropora corals developed gametes directly from those tissues 15,16 . However, 74% of the SNVs that we identified in parent tissue were also present in the sperm spawned from that branch, and 26% were not.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…If we had found only separate parent and sperm SNVs this would have shown that Acropora corals have classical Weismannian germ and somatic cell lineage differentiation at the embryonic stage, which has been suggested previously 17 . Likewise, if we had found that all parent tissue SNVs were also in the sperm, we would have concluded that Acropora corals developed gametes directly from those tissues 15,16 . However, 74% of the SNVs that we identified in parent tissue were also present in the sperm spawned from that branch, and 26% were not.…”
mentioning
confidence: 98%
“…If these mutations are inherited by the coral's gametes, they must increase the heritable mutational load of these animals. Some previous studies identified putative somatic mutations in the gametes or juvenile offspring of mutant parents 15,16 , but others have reported absence of somatic mutations in the gametes 17 . Wilcox test (two-tailed, paired) Parent Only, GOH Full: 4.4 x10 -7 ± 0.6 x10 -7 Coding: 9.2 x10 -8 ±3.1 x10 -8 V=28, P= 0.016…”
mentioning
confidence: 99%
“…The standing genetic diversity of corals is presumably large [71][72][73][74] , suggesting a capacity to recover from reductions in population size under suitable conditions, at least for some species 73 . Corals could also have the capacity to adapt via heritable somatic mutations 75,76 . The ability to rapidly adapt (years to decades) to changing environments is further supported by the presence and frequency of thermotolerance alleles and the modeling of population trajectories under different climate change scenarios 72,77 .…”
Section: Key Pointsmentioning
confidence: 99%